Trichloroethene (TCE) hydrodechlorination by NiFe nanoparticles: Influence of aqueous anions on catalytic pathways. (August 2018) - Han, Yanlai; Liu, Changjie; Horita, Juske; Yan, Weile
Abstract: Amending bulk and nanoscale zero-valent iron (ZVI) with catalytic metals significantly accelerates hydrodechlorination of groundwater contaminants such as trichloroethene (TCE). The bimetallic design benefits from a strong synergy between Ni and Fe in facilitating the production of active hydrogen for TCE reduction, and it is of research and practical interest to understand the impacts of common groundwater solutes on catalyst and ZVI functionality. In this study, TCE hydrodechlorination reaction was conducted using fresh NiFe bimetallic nanoparticles (NiFe BNPs) and those aged in chloride, sulfate, phosphate, and humic acid solutions with concurrent analysis of carbon fractionation of TCE and its daughter products. The apparent kinetics suggest that the reactivity of NiFe BNPs is relatively stable in pure water and chloride or humic acid solutions, in contrast to significant deactivation observed of PdFe bimetallic particles in similar media. Exposure to phosphate at greater than 0.1 mM led to a severe decrease in TCE reaction rate. The change in kinetic regimes from first to zeroth order with increasing phosphate concentration is consistent with consumption of reactive sites by phosphate. Despite severe kinetic effect, there is no significant shift in TCE 13 C bulk enrichment factor between the fresh and the phosphate-aged particles. Instead, pronounced retardation of TCE reaction by NiFe BNPs in deuterated water (D2 O) points to the importance of hydrogen spillover in controlling TCE reduction rate by NiFe BNPs, and such process can be strongly affected by groundwater chemistry. Highlights: NiFe nanoparticles are sensitive to a different suite of groundwater solutes compared to PdFe. NiFe nanoparticles are relatively stable in the presence of chloride and NOM. NiFe nanoparticles are moderately deactivated by sulfate and strongly inhibited by phosphate ions. Multiple lines of investigations suggest the importance of hydrogen activation and migration in TCE reduction by NiFe nanoparticles.